(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Food is one of the most essential aspects of existence and a fundamental need for all livingthings. Many foods are now tainted by various additives. An adulterant diminishes the significance offood. In order to compete with the market, adulterants such as metanil yellow (an artificial hue) and chalkpowder, brick powder, and hazardous compounds have been added to turmeric powder. Anemia,paralysis, brain damage, stomach issues, and cancer may all result from ingesting food tainted with thesesubstances, according to a recent research. Experience in filing food-adulteration allegations Foodadulteration accusations aren’t being filed because of these reasons. The respondents’ domicile, socialworth, and purchasing habits, as well as Food contamination